Case Report: Presumed cerebral salt wasting syndrome in a 10-week-old German Shorthaired Pointer - Jackson, Elizabeth; Fefer, Gilad; Muñana, Karen R.; Hansen, Bernie D. (Frontiers in Veterinary Science, 2025)
This case report describes a rare presentation of cerebral salt-wasting syndrome (CSW) in a 10-week-old German Shorthaired Pointer following a traumatic brain injury. The patient presented stuporous and tetraplegic with advanced imaging revealing a depressed skull fracture and active brain hemorrhage. Following surgical intervention, the dog exhibited persistent hypovolemia and hyponatremia prompting treatment with intravenous hypertonic saline and enteral sodium supplementation. Positive response to sodium supplementation, coupled with elevated fractional excretion of uric acid (FEUA) despite clinical improvement, supported the diagnosis of CSW. This report contributes novel insights into CSW in veterinary medicine, emphasizing the distinctive features of its presentation, diagnostic considerations, and treatment responses. The clinical utility of FEUA as a diagnostic tool is highlighted for the first time in a canine patient, providing a valuable tool for differentiation. This information enhances veterinary practitioners’ awareness, facilitating more accurate diagnoses and tailored treatment strategies for similar cases in the future.